Investigation on Optimum Bitumen Content of Asphaltic Concrete-Mix (ACW 14) with Replacement of Fine Aggregates with LDPE - Shahbaz, Ahmed Memon (2017)
50% Partial replacement aggregate of Size 75um and < 75um been done with low density polyethylene. 4%, 5% , 6% and 7% bitumen content by weight of aggregates has been added to design mix for Asphaltic Concrete Wearing Course 14mm design, the result show that at optimum bitumen content of 5.78% by weight of aggregates the stability is 14200N which above 13000N minimum required. Flow is 4.8mm which is within the range of 2mm-5mm required. Voids filled with bitumen (VFB) are 67% also within range of 65%-75% and Voids in total mix are 68% which are at the border of the range 3.0% - 7.0% which is acceptable. Overall the performance of the design mix is satisfactory and complainant.